Socio Demographic Profile and Risperidone Response in New Versus Old Schizophrenia Patients - Belbase, Mohan; Adhikari, Jyoti (Journal of Nepalgunj Medical College, 2020)
Introduction: Schizophrenia is a mental disorder characterized with disorganized thinking, perception, expression of reality with significant social and occupational dysfunction. Two groups of drugs are in recent use namely first generation (typicals) and second generation (atypical) antipsychotics. Risperidone is a broad spectrum antipsychotic and has a role as a first-line agent for first break, mild to moderately ill patients and for severely ill treatment–refractory patients. Aims: This article tries to compare the risperidone response in newly diagnosed schizophrenia patients versus old patients already on some antipsychotics other than risperidone. Methods: This is an experimental intervention study of patients attending to psychiatry OPD and indoor in Nepalgunj Medical College, Kohalpur. Total 40 patients (27 new and 13 old) were selected and sample was collected in one year from January 2018 till December 2018. Positive and negative syndrome scale questionnaire was used to record the positive and negative symptoms of schizophrenia on baseline (week 0). Patients were followed up on week 4 and week 8 and the same positive and negative syndrome scale questionnaire was applied to record the improvement. Risperidone was given in therapeutic dose (4-8mg) on the basis of symptoms and improvement. Results: The study subjects were divided into new N=27 (17 male and 10 female) and old N=13 (7 male and 6 female). Maximum number of schizophrenia cases were in age group 15-25 and 35-44 years comprising 30 % in each group. Mean total duration of illness in new group was 23.89 ± 29.51 months (median being 12.0 months) while in old group it was 123.69 ± 83.34 months (median being 96.0 months) with significant difference between two groups (p= <0.001).The mean risperidone dose in milligram on base line (week 0) was 4.15 ± 0.55 for old group while it was 4.04 ± 0.52 for new group. On week 4, the mean dose for old group was 5.08 ± 0.95 while for the new group it was 4.81 ± 1.08. On week 8, the dose for old group was 6.08 ± 1.32 while it was 5.15 ± 1.35 for new group. There was a significant difference in the drug dose on week 8 between old group and new group with p value of 0.047 (statistically significant). Conclusion: Our study suggests that schizophrenia is found in most productive age group. Risperidone is effective in both new and old schizophrenia patients however old patients need higher dose of risperidone than new patients.